PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Naya, Rudsyah; Sugiyono, Sugiyono; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to know the influence of the Scramble type of cooperative model in student achievement on social science learning tin fifth grade V students of Elementary School 30 Pontianak Selatan. The method used is experimental method. Form of pre-experimental design, type of experiment one group pretest posttest design. The population in this study is all students of class V Elementary School Pontianak Selatan 30 which consists of 1 classes, which amounted to 30 students. The sample is a V class of 30 students. Data collection techniques used are measurement techniques. Data collection tool in the form of test with multiple choice form amounted to 50 problem.The result of the research is the average pre-test score 60,93, meanwhile post-test 70,4, t Test price tcount compared with ttable with dk = 30-1 = 29 and significant level (?) 0,01 obtained ttable price = 2.756, it turns thitung ? ttable or 3,412 10,53 ? 2,756 means significant, it is concluded that Ho is rejected, on the contrary Ha accepted. Thus it can be concluded that, there is influence the use of cooperative model of Scramble type on the learning outcomes of class V students of State Elementary School 30 Pontianak Selatan. The result of effect size (ES) was 0,71 medium criterion. The influence of the use of cooperative model of Scramble the students?s learning outcomes on Five Grade Elementary School. Keywords: Influence Scramble Learning Outcomes.